ANALISIS ASUHAN KEPERAWATAN KELUARGA DENGAN REMAJA YANG KECANDUAN GAME ONLINE DENGAN INTERVENSI INOVASI METODE TOKEN EKONOMI DI RW 0011 JATIRANGGON BEKASI - Siti Alifah Nadia Putri (2023)
Playing too many online games can make you addicted. This addiction can cause problems like trouble sleeping because your brain, eyes, and nerves are overworked. The token economy system helps to solve the issue of teenagers being addicted to online games. This research wants to find out if family nursing care combined with the token economy method can help teenagers in RW 001 Jatiranggon Bekasi Village who are addicted to online games. We helped two teenagers in Bekasi who spent too much time playing online games using a method called token economy. From January 15 to 27, 2023, we did an activity called "token economy" in 4 meetings that lasted an hour each. The token system helped two teenagers to improve their understanding of online game addiction after four tries. The two young people learned more and played less video games. Using a reward system helped them overcome addiction to online games. Nurses who work with families and communities should know how to use the token economy method to help teenagers who are addicted to online games.